Optimization of base-catalyzed ethyl ester production from palm oil - Shahla, S.; Ngoh, G.C.; Yusoff, Rozita (Wiley, 2012)
Plant-based ethyl esters can be used directly as biodiesel or as a bio-resource for other industries such as lubricant and detergents. In this work, production of ethyl ester from chemical transesterification of palm oil with ethanol using sodium ethoxide as catalyst has been optimized by Box-Behnken design and response surface methodology. Catalyst concentration was found to be the most significant parameter affecting the conversion rate of the reaction. The interaction of temperature and molar ratio of ethanol to palm oil had minor effect on the conversion rate. A reduced cubic model was developed to navigate the design space. It was predicted by the model at optimum reaction conditions, that is 1.2?wt of sodium ethoxide and 12:1 molar ratio of ethanol to oil at 25?degrees C, that as high as 98 ethyl ester can be achieved. It was then verified experimentally that close to 100 conversion rate is achievable under these optimum conditions.